Preparation method of crystal glass ornament with diamond-like coating on surface

The deposit of diamond-like films through vacuum coating technology solves the problem that traditional crystal glass jewelry coatings are difficult to achieve gem gloss, and achieves the improvement of high quality, wear resistance and gloss. They are suitable for jewelry surface treatments of various materials.

CN119465043APending Publication Date: 2025-02-18SHAANXI IAN BUNENG CARBON BASED TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411654435.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional crystal glass jewelry coating technology is difficult to achieve the gem luster and appearance, and the process is complex and costly, making it difficult to achieve.

Method used

Using vacuum coating technology, diamond-like films are deposited through graphite targets and filtered cathode vacuum arc technology to form a uniform and dense film, improving the wear resistance and gloss of crystal glass jewelry.

Benefits of technology

It realizes the gem luster and appearance of crystal glass jewelry, enhances its durability and texture, has a safe and reliable process, and is suitable for jewelry surface treatment of various materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465043A_ABST
    Figure CN119465043A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a crystal glass ornament with a diamond-like coating on the surface, and relates to the technical field of vacuum coating, and the preparation method comprises the following steps: S1, pretreating the surface of the ornament, cleaning and polishing the surface of the ornament to ensure that the surface is free of greasy dirt, dust and other impurities; s2, preparing a graphite target material, selecting high-purity graphite as a target material, and mounting the target material at the position of an anode cylinder target material of coating equipment; and S3, preparing a vacuum environment: placing the jewelry in a vacuum chamber, and vacuumizing to preset pressure to ensure the purity of the deposition environment. According to the diamond-like carbon film prepared through the method, the texture can be improved, adverse effects on crystal glass jewelry cannot be generated in the preparation process, the process is safe and reliable, the filtered cathode vacuum arc technology is adopted, impurities in a graphite target material are effectively removed, the purity and quality of the deposited film are improved, and the diamond-like carbon film is suitable for surface treatment of jewelry made of various materials; and the method has good universality and adaptability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of vacuum coating, and in particular to a method for preparing a crystal glass ornament with a diamond-like coating on the surface. Background Art

[0002] Crystal glass jewelry refers to various ornaments made of crystal glass. It has the characteristics of high transparency, high refractive index, high hardness, etc. It has exquisite appearance and elegant texture. It is often used to make jewelry, ornaments, and handicrafts. Traditionally, crystal is often enhanced by preparing the same materials as gemstones and doping with the same elements. The outer surface of the crystal glass jewelry is cleaned in advance, and then a mixture of silicon and aluminum is used as a target material to plate a transition layer on the surface of the jewelry. Non-ferrous metals are used as targets, and the first metal layer, i.e., the color layer, is plated on the transition layer to enhance the strength and wear resistance of the crystal glass jewelry. However, the effect of the finished product after coating is limited. Although the colors are diverse, it is difficult to present the luster and appearance of real gemstones. This is because the color of real gemstones is generally doped with different kinds of elements, and the natural effect is achieved through absorption, refraction, and reflection of the incident light. Traditional coating methods are often difficult to achieve this effect of natural gemstones. The preparation cost is high, the process is complex, and the implementation is difficult. In this regard, we propose a preparation method for crystal glass jewelry with a surface diamond-like coating. Summary of the invention

[0003] In order to solve the above technical problems, a method for preparing crystal glass ornaments with a diamond-like coating on the surface is provided. This technical solution solves the above problems.

[0004] To achieve the above purpose, the technical solution adopted by the present invention is: a method for preparing a crystal glass ornament with a surface diamond-like coating, the preparation steps are: S1. Pre-treatment of jewelry surface: cleaning and polishing the jewelry surface to ensure that the surface is free of oil, dust and other impurities; S2. Graphite target material preparation: high-purity graphite is selected as the target material and installed in the anode cylinder target position of the coating equipment; S3, vacuum environment preparation, placing the jewelry in the vacuum chamber, evacuating to a predetermined pressure to ensure the purity of the deposition environment; S4, surface ion cleaning, turn on the argon ion source power supply, generate a large number of argon ions through discharge, control the argon ions through electromagnetic field to accelerate and bombard the jewelry surface, so as to achieve the cleaning effect of the jewelry surface and further clean the jewelry surface; S5, application of filtered cathode vacuum arc technology, starting the power supply, generating an arc, gasifying the graphite target, removing impurities through the filtration system, and forming pure carbon vapor; S6, diamond-like film deposition, carbon ions are deposited on the surface of jewelry to form a uniform and dense diamond-like film; S7, post-processing, cleaning and wiping the jewelry after deposition; S8. Quality inspection: perform quality inspection on the prepared coating.

[0005] Preferably, in step S1, when processing the jewelry, cleaning and polishing are performed in advance. In the cleaning step, a jewelry cleaner is selected for cleaning, and the jewelry is placed in a container containing the cleaner for soaking for 10 minutes to 15 minutes. After the soaking is completed, the jewelry is taken out and the outer surface and gaps are cleaned with a brush. After the cleaning is completed, it is rinsed with clean water and wiped, wherein the jewelry cleaner is 75% alcohol; in the polishing step, a polishing paste is prepared, applied to the outer surface of the jewelry, and polished with a polishing wheel, and rough polishing and fine polishing are repeated. After the polishing is completed, the jewelry is wiped with a clean soft cloth, and cleaned with anhydrous alcohol and an ultrasonic cleaner for 5 minutes, and then cleaned with deionized water and ultrasonic for 5 minutes.

[0006] Preferably, the vacuum range in step S3 is 5.0x10 -3 Pa-5.0x10 -4 Pa, in this environment, reduce the interference of impurities in the air on the precipitation process, and the ambient temperature is 20℃-30℃; the vacuum step is to check the sealing of the vacuum chamber, put the jewelry in the vacuum chamber, turn on the vacuum pump, and pump out the air in the room. After reaching the predetermined pressure, perform a vacuum holding test, close the valve between the vacuum pump and the vacuum chamber, and observe whether the reading of the vacuum gauge can remain stable. If the pressure rises, it indicates that there is a leak in the vacuum chamber, and it should be checked and repaired in time.

[0007] Preferably, the purity of graphite in step S2 is not less than 99.995%, and the density of the graphite target is not less than 2.0 g / cm 3 The installation steps are as follows: clean the anode cylinder of the equipment, wipe the inner surface of the anode cylinder with anhydrous ethanol, place the target on the cathode seat, align it with the cathode seat using the thread of the graphite target, connect it to the cooling system, and finally check the installation of the target.

[0008] Preferably, in step S5, as the power is turned on, the current flows in the circuit inside the device to form a strong electric field. When the electric field strength reaches a level sufficient to break through the rarefied gas in the vacuum environment, an arc is generated near the graphite target and acts on the graphite target. Under the high temperature burning of the arc, the chemical bonds between atoms begin to break, the solid graphite is gradually vaporized, and the graphite atoms are separated from the surface of the target to form plasma, which is guided to the filtration system to filter out impurities and form pure carbon ions.

[0009] Preferably, in step S6, after obtaining pure carbon ions, they are guided to the surface of the jewelry, and deposited and accumulated on the surface of the jewelry under the synergistic effect of temperature, pressure and electric field conditions. Through process control, the deposition speed and angle of carbon atoms are precisely regulated, and they are connected to each other through strong covalent bonds, gradually forming a continuous and dense film to obtain a thin film.

[0010] Preferably, in step S7, the jewelry after deposition is cleaned again, and the cleaned jewelry is dried by air drying.

[0011] Preferably, the detection in step S8 includes detection of hardness, thickness, wear resistance and bonding strength. The hardness detection is based on a nano indenter, the thickness detection is based on an optical microscopy method, the wear resistance detection is based on a friction and wear test method, and the bonding strength detection is based on a scratch method bonding strength detection.

[0012] Preferably, the optical microscopy method is to prepare the jewelry sample with coating appropriately to expose the cross section of the coating, and then observe it under an optical microscope to determine the coating thickness by measuring the vertical distance from the interface between the coating and the substrate to the coating surface; The friction and wear test method uses a friction and wear tester to put the jewelry sample with diamond-like coating in contact with a counter-abrasive material, and rub it under a load of 1N-10N and a rotation speed of 100rpm-1000rpm. After 1h-10h, the wear volume or weight loss of the coating is measured to evaluate its wear resistance; The scratch method for bonding strength testing is to use a scratch tester to scratch a scratch on the coating surface and observe the peeling of the coating during the scratching process. The acoustic emission detection technology is used to monitor the acoustic signal generated during the scratching process. When the coating peels off, a specific acoustic emission signal will be generated. The bonding strength between the coating and the substrate is evaluated based on the critical load and peeling morphology of the coating peeling.

[0013] Compared with the prior art, the present invention has the following beneficial effects: The anti-corrosion and wear-resistant properties of the diamond-like film prepared by the present invention have been verified in the industrial field. When applied to the surface of jewelry, the durability of the jewelry can be improved. The diamond-like film can make the original material of the crystal glass have a gem luster and improve the texture. During the preparation process, no adverse effects are produced on the crystal glass jewelry. The process is safe and reliable. The filtered cathode vacuum arc technology is used to effectively remove impurities in the graphite target material, improve the purity and quality of the deposited film, and is suitable for the surface treatment of jewelry made of various materials, with good versatility and adaptability. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The present invention is a flow chart of the steps for preparing the coating. DETAILED DESCRIPTION

[0015] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0016] Example 1 S1. Pre-treatment of jewelry surface: cleaning and polishing the jewelry surface to ensure that the surface is free of oil, dust and other impurities; S2. Graphite target material preparation: high-purity graphite is selected as the target material and installed in the anode cylinder target position of the coating equipment; S3, vacuum environment preparation, placing the jewelry in the vacuum chamber, evacuating to a predetermined pressure to ensure the purity of the deposition environment; S4, surface ion cleaning, turn on the argon ion source power supply, generate a large number of argon ions through discharge, control the argon ions through electromagnetic field to accelerate and bombard the jewelry surface, so as to achieve the cleaning effect of the jewelry surface and further clean the jewelry surface; S5, application of filtered cathode vacuum arc technology, starting the power supply, generating an arc, gasifying the graphite target, removing impurities through the filtration system, and forming pure carbon vapor; S6, diamond-like film deposition, carbon ions are deposited on the surface of jewelry to form a uniform and dense diamond-like film; S7, post-processing, cleaning and wiping the jewelry after deposition; S8. Quality inspection: perform quality inspection on the prepared coating.

[0017] The film prepared in this application has undergone quality testing to ensure that the hardness and wear resistance of the diamond-like film meet the expected standards. High-quality diamond-like films can effectively resist friction and scratches during daily wear, reduce damage to the surface of jewelry, and thus extend the service life of jewelry. Clear quality inspection indicators help to establish a standardized production process, which enables different batches of jewelry coating preparation processes to follow the same quality standards and reduce fluctuations in product quality.

[0018] In step S1, when handling jewelry, pre-cleaning and polishing are performed. In the cleaning step, jewelry is cleaned by selecting a jewelry cleaner, and the jewelry is placed in a container filled with the cleaner for soaking for 10-15 minutes. After soaking, the jewelry is taken out and the outer surface and gaps are cleaned with a brush. After cleaning, it is rinsed with clean water and wiped. The jewelry cleaner is 75% alcohol; Polishing steps: prepare the polishing paste, apply it on the outer surface of the jewelry, use the polishing wheel for polishing, repeat the rough polishing and fine polishing. After polishing, wipe the jewelry with a clean soft cloth, use anhydrous alcohol and ultrasonic cleaning machine to clean for 5 minutes, and then use deionized water and ultrasonic cleaning for 5 minutes.

[0019] The present application cleans the jewelry in advance to provide a clean substrate for the deposition of the diamond-like carbon film, which enables the film to better adhere to the surface of the jewelry, enhances the bonding force between the film and the jewelry, and avoids peeling of the film during use.

[0020] The vacuum range in step S3 is 5.0x10 -3 Pa-5.0x10 -4 Pa, in this environment, reduce the interference of impurities in the air on the precipitation process, and the ambient temperature is 20℃-30℃; the vacuum step is to check the sealing of the vacuum chamber, put the jewelry in the vacuum chamber, turn on the vacuum pump, and pump out the air in the room. After reaching the predetermined pressure, perform a vacuum holding test, close the valve between the vacuum pump and the vacuum chamber, and observe whether the reading of the vacuum gauge can remain stable. If the pressure rises, it indicates that there is a leak in the vacuum chamber, and it should be checked and repaired in time.

[0021] This application greatly reduces the number of air molecules. This means that during the deposition of diamond-like films, the interference of oxygen, nitrogen, and water vapor impurities in the air on the deposition process is almost eliminated, and at this vacuum degree and temperature, some gases are prevented from corroding jewelry and films.

[0022] The purity of graphite in step S2 is not less than 99.995%, and the density of graphite target is not less than 2.0g / cm 3 The installation steps are as follows: clean the anode cylinder of the equipment, wipe the inner surface of the anode cylinder with anhydrous ethanol, place the target on the cathode seat, align it with the cathode seat using the thread of the graphite target, connect it to the cooling system, and finally check the installation of the target.

[0023] The present application ensures that during the magnetron sputtering process, the carbon vapor produced by gasification has few impurities. A high-purity carbon source is essential for forming a high-quality diamond-like film because the presence of impurities may change the physical and chemical properties of the film. The density of the graphite target is in the range of 1.5g / cm³-2.2g / cm³. The graphite structure of this density is compact and can stably release graphite atoms when bombarded by ions.

[0024] In step S5, as the power is turned on, the current flows in the circuit inside the equipment, forming a strong electric field. When the electric field strength is sufficient to break through the rarefied gas in the vacuum environment, an arc is generated near the graphite target and acts on the graphite target. Under the high temperature burning of the arc, the chemical bonds between atoms begin to break, the solid graphite is gradually vaporized, and the graphite atoms are separated from the surface of the target to form plasma, which is guided to the filtration system to filter out impurities and form pure carbon ions.

[0025] The pure carbon vapor formed after the impurities are removed by the filtering system in this application is the key to preparing high-quality diamond-like films. During the deposition process, pure carbon vapor can ensure the formation of a film with a single composition and uniform structure on the surface of the jewelry. If the carbon vapor contains impurities, these impurities may be mixed in the film, causing defects in the film. Under the action of the electric field and the electric arc, the graphite target material is stably gasified to produce carbon vapor, and after continuous treatment by the filtering system, a stable carbon vapor flow can be provided for the deposition process.

[0026] In step S6, after obtaining pure carbon ions, they are guided to the surface of the jewelry. Under the synergistic effect of temperature, pressure and electric field conditions, they are deposited and accumulated on the surface of the jewelry. Through process control, the deposition speed and angle of carbon atoms are precisely regulated. They are connected to each other through strong covalent bonds, gradually forming a continuous and dense film to obtain a thin film.

[0027] The present application forms a continuous and dense diamond-like film with excellent hardness and wear resistance by precisely controlling the deposition speed and angle of carbon atoms. Its hardness is close to that of natural diamonds, which enables the jewelry to effectively resist various frictions and scratches during daily wear. For example, when it comes into contact with clothing or other objects, the film can protect the jewelry base from damage, greatly extending the service life of the jewelry. Since the deposition angle of carbon atoms can be precisely controlled, perfect film deposition can be achieved for jewelry of various complex shapes, such as jewelry with fine carvings, hollows or irregular surfaces.

[0028] In step S7, the jewelry after deposition is cleaned again, and the cleaned jewelry is dried by air drying.

[0029] After the deposition process of this application, some chemicals used for deposition, tiny particles or reaction by-products may remain on the surface of the jewelry. Cleaning again can ensure that these impurities are completely removed. For example, if electroplating deposition is used, metal ions in the electroplating solution may be unevenly attached to the surface of the jewelry, or additives that do not participate in the reaction may remain. Cleaning can restore the jewelry to a pure surface state. The surface of the jewelry after cleaning is smoother and cleaner, which can improve the gloss and overall appearance of the jewelry. This is very important for jewelry whose main value is beauty, such as precious metal jewelry such as gold and silver. After cleaning, it can be made more dazzling and more in line with consumers' expectations for high-quality jewelry. Residual chemicals may react chemically with jewelry materials and cause corrosion. Some deposition reagents containing acidic or alkaline components, if left on the surface of jewelry, may corrode metal jewelry and reduce the quality and service life of the jewelry. Cleaning can avoid this situation; Compared with drying, air drying is a gentler drying method. Drying may damage jewelry due to high temperatures, especially for jewelry containing gemstones or special materials. For example, some organic gemstones are sensitive to temperature, and high-temperature drying may cause discoloration, cracking and other damage. Air drying can avoid such heat damage and ensure the integrity of the jewelry.

[0030] Example 2 Jewelry coating steps are: A1. Clean and polish the jewelry to remove impurities; A2. Select the material for coating; A3. Use chemical plating to coat the jewelry; A4. Post-process the coated jewelry, including cleaning and drying.

[0031] The chemical reaction in the chemical plating process in Example 2 is relatively complex, and it is sometimes difficult to accurately control the thickness and uniformity of the coating. Uneven coating thickness may cause inconsistent color of the jewelry, affecting the appearance. If the coating is too thick, the film may crack or peel off. The environmental requirements are high and the operation is inconvenient. Example 1 uses filtered cathode vacuum arc technology to effectively remove impurities in the graphite target and improve the purity and quality of the deposited film. It is suitable for the surface treatment of jewelry made of various materials and has good versatility and adaptability.

[0032] Table 1 below shows the properties of the films prepared in Example 1 and Comparative Example 1.

[0033] Table 1 Hardness testing The test is based on the nanoindenter. The prepared sample is placed under the instrument, and the parameters of the instrument are set. According to the set parameters, the nanoindenter is started to start the loading process. The indenter will gradually apply pressure to the sample surface at the set loading rate until the set load size is reached. During the loading process, the instrument will record the load and displacement data in real time, and record and analyze the data.

[0034] Thickness detection Optical microscopy method: The jewelry sample with coating is properly prepared to expose the cross section of the coating, and then observed under an optical microscope. The coating thickness is determined by measuring the vertical distance from the interface between the coating and the substrate to the coating surface.

[0035] Wear resistance test The friction and wear test method uses a friction and wear tester to put the jewelry sample with diamond-like coating in contact with a grinding material, and rub it under a load of 1N-10N and a rotation speed of 100rpm-1000rpm. After 1h-10h, its wear resistance is evaluated by measuring the wear volume or weight loss of the coating.

[0036] Binding strength test The scratch method for bonding strength testing is to use a scratch tester to scratch a scratch on the coating surface and observe the peeling of the coating during the scratching process. The acoustic emission detection technology is used to monitor the acoustic signal generated during the scratching process. When the coating peels off, a specific acoustic emission signal will be generated. The bonding strength between the coating and the substrate is evaluated based on the critical load and peeling morphology of the coating peeling.

[0037] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention claimed.

Claims

1. A method for preparing a crystal glass ornament with a surface diamond-like coating, characterized in that: The preparation steps are: S1. Pre-treatment of jewelry surface: cleaning and polishing the jewelry surface to ensure that the surface is free of oil, dust and other impurities; S2. Graphite target material preparation: high-purity graphite is selected as the target material and installed in the anode cylinder target position of the coating equipment; S3, vacuum environment preparation, placing the jewelry in the vacuum chamber, evacuating to a predetermined pressure to ensure the purity of the deposition environment; S4, surface ion cleaning, turn on the argon ion source power supply, generate a large number of argon ions through discharge, control the argon ions through electromagnetic field to accelerate and bombard the jewelry surface, so as to achieve the cleaning effect of the jewelry surface and further clean the jewelry surface; S5, application of filtered cathode vacuum arc technology, starting the power supply, generating an arc, gasifying the graphite target, removing impurities through the filtration system, and forming pure carbon vapor; S6, diamond-like film deposition, carbon ions are deposited on the surface of jewelry to form a uniform and dense diamond-like film; S7, post-processing, cleaning and wiping the jewelry after deposition; S8. Quality inspection: perform quality inspection on the prepared coating.

2. The method for preparing a crystal glass ornament with a surface diamond-like coating according to claim 1, characterized in that: In step S1, when handling jewelry, pre-cleaning and polishing are performed. In the cleaning step, jewelry is cleaned by selecting a jewelry cleaner, and the jewelry is placed in a container filled with the cleaner for soaking for 10-15 minutes. After soaking, the jewelry is taken out and the outer surface and gaps are cleaned with a brush. After cleaning, it is rinsed with clean water and wiped. The jewelry cleaner is 75% alcohol; Polishing steps: prepare the polishing paste, apply it on the outer surface of the jewelry, use the polishing wheel for polishing, repeat the rough polishing and fine polishing. After polishing, wipe the jewelry with a clean soft cloth, use anhydrous alcohol and ultrasonic cleaning machine to clean for 5 minutes, and then use deionized water and ultrasonic cleaning for 5 minutes.

3. The method for preparing a crystal glass ornament with a surface diamond-like coating according to claim 1, characterized in that: The vacuum range in step S3 is 5.0x10 -3 Pa-5.0x10 -4 Pa, in this environment, reduce the interference of impurities in the air on the precipitation process, and the ambient temperature is 20℃-30℃; the vacuum step is to check the sealing of the vacuum chamber, put the jewelry in the vacuum chamber, turn on the vacuum pump, and pump out the air in the room. After reaching the predetermined pressure, perform a vacuum holding test, close the valve between the vacuum pump and the vacuum chamber, and observe whether the reading of the vacuum gauge can remain stable. If the pressure rises, it indicates that there is a leak in the vacuum chamber, and it should be checked and repaired in time.

4. The method for preparing a crystal glass ornament with a surface diamond-like coating according to claim 1, characterized in that: The purity of graphite in step S2 is not less than 99.995%, and the density of graphite target is not less than 2.0g / cm 3 The installation steps are as follows: clean the anode cylinder of the equipment, wipe the inner surface of the anode cylinder with anhydrous ethanol, place the target on the cathode seat, align it with the cathode seat using the thread of the graphite target, connect it to the cooling system, and finally check the installation of the target.

5. The method for preparing a crystal glass ornament with a surface diamond-like coating according to claim 1, characterized in that: In step S5, as the power is turned on, the current flows in the circuit inside the equipment, forming a strong electric field. When the electric field strength is sufficient to break through the rarefied gas in the vacuum environment, an arc is generated near the graphite target and acts on the graphite target. Under the high temperature burning of the arc, the chemical bonds between atoms begin to break, the solid graphite is gradually vaporized, and the graphite atoms are separated from the surface of the target to form plasma, which is guided to the filtration system to filter out impurities and form pure carbon ions.

6. The method for preparing a crystal glass ornament with a surface diamond-like coating according to claim 1, characterized in that: In step S6, after obtaining pure carbon ions, they are guided to the surface of the jewelry. Under the synergistic effect of temperature, pressure and electric field conditions, they are deposited and accumulated on the surface of the jewelry. Through process control, the deposition speed and angle of carbon atoms are precisely regulated. They are connected to each other through strong covalent bonds, gradually forming a continuous and dense film to obtain a thin film.

7. The method for preparing a crystal glass ornament with a surface diamond-like coating according to claim 1, characterized in that: In step S7, the jewelry after deposition is cleaned again, and the cleaned jewelry is dried by air drying.

8. The method for preparing a crystal glass ornament with a surface diamond-like coating according to claim 1, characterized in that: The tests in step S8 include hardness test, thickness test, wear resistance test and bonding strength test. The hardness test is based on nano indentation test, the thickness test is based on optical microscopy, the wear resistance test is based on friction and wear test method, and the bonding strength test is based on scratch test.

9. The method for preparing a crystal glass ornament with a surface diamond-like coating according to claim 8, characterized in that: Optical microscopy method: The jewelry sample with coating is properly prepared to expose the cross section of the coating, and then observed under an optical microscope. The coating thickness is determined by measuring the vertical distance from the interface between the coating and the substrate to the coating surface.

10. The method for preparing a crystal glass ornament with a surface diamond-like coating according to claim 9, characterized in that: The friction and wear test method uses a friction and wear tester to put the jewelry sample with diamond-like coating in contact with a counter-abrasive material, and rub it under a load of 1N-10N and a rotation speed of 100rpm-1000rpm. After 1h-10h, the wear volume or weight loss of the coating is measured to evaluate its wear resistance; The scratch method for bonding strength testing is to use a scratch tester to scratch a scratch on the coating surface and observe the peeling of the coating during the scratching process. The acoustic emission detection technology is used to monitor the acoustic signal generated during the scratching process. When the coating peels off, a specific acoustic emission signal will be generated. The bonding strength between the coating and the substrate is evaluated based on the critical load and peeling morphology of the coating peeling.